2014
DOI: 10.1063/1.4893314
|View full text |Cite
|
Sign up to set email alerts
|

Global gyrokinetic stability of collisionless microtearing modes in large aspect ratio tokamaks

Abstract: Linear full radius gyrokinetic calculations show the existence of unstable microtearing modes (MTMs) in purely collisionless, high temperature, large aspect ratio tokamak plasmas. The present study takes into account fully gyrokinetic highly passing ions and electrons. The global 2-D structures of the collisionless mode with full radius coupling of the poloidal modes is obtained and compared with another electromagnetic mode, namely, the Alfvén Ion Temperature Gradient (AITG) mode (or Kinetic Ballooning Mode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…[14] pertaining to a spherical tokamak with high-β plasma, the magnetic drift resonance of trapped electrons is found to drive the collisionless MTM instability. At larger aspect ratios, the fraction of trapped particles is relatively small, and it has been found that collisionless MTM is driven unstable by the magnetic drift resonance of highly passing electrons [15]. Ions dynamics, on the other hand, do not affect the mode significantly.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…[14] pertaining to a spherical tokamak with high-β plasma, the magnetic drift resonance of trapped electrons is found to drive the collisionless MTM instability. At larger aspect ratios, the fraction of trapped particles is relatively small, and it has been found that collisionless MTM is driven unstable by the magnetic drift resonance of highly passing electrons [15]. Ions dynamics, on the other hand, do not affect the mode significantly.…”
Section: Introductionmentioning
confidence: 95%
“…In this work, many of the recent results described in Ref. [15] will be elaborated, where it is shown that passing electron alone suffice to drive MTM unstable in large aspect ratio tokamaks. In the later part, the effect of trapped electrons is addressed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations